COMPARATIVE CONTRIBUTION OF COGNITIVE FACTORS AND SELF-ATTITUDE TO SOCIAL PERCEPTION OF OUTGROUPS OF DIFFERENT TYPES - Milena V Baleva; Vera A Gasimova; Galina V Kovaleva (Peoples' Friendship University of Russia (RUDN University), 2018)
The research introduces the idea of the integrative approach to the social perception, which is regarded, firstly, from the point of cognitive and motivational approaches, and secondly, as the result of internal and external factors interaction. The contributions of cognitive styles, divergent thinking, and self-attitude to outgroup stereotyping and ingroup bias are studied. These contributions are compared in conditions of different artificial groups perception. The discriminant models of stereotyping and bias are constructed and analyzed in terms of cognitive variables and self-attitude. 155 students of the Perm State University from 17 to 22 years old (M = 18.90, SD = 0.96), including 113 females (72.9%) and 42 males (27.1%), participated in the research. The description of social groups was presented in specially constructed texts. The measuring of social perception was implemented with verbal procedures based on the understanding of bias as ingroup prototypicality and stereotyping - as a tendency to describe the Other through generalized features, rather than actual behavior. The selfattitude and cognitive variables were measured using standardized methods. It was found that the predominant contribution to stereotyping belonged to cognitive styles and, first of all, to the fielddependence. On the contrary, cognitive styles did not play the decisive role in the formation of ingroup bias (favoritism), while the indicators of self-attitude facilitated its manifestations. The divergent thinking significantly contributed to both stereotyping and bias. Its influence varied depending on the group type. These results could be useful in the development of psychological corrective programs aimed at reducing the negative manifestations of intergroup interaction.